2014
DOI: 10.5350/dajpn2014270403
|View full text |Cite
|
Sign up to set email alerts
|

Test anxiety prevalance and related variables in the students who are going to take the university entrance examination

Abstract: Test anxiety prevalance and related variables in the students who are going to take the university entrance examinationObjective: Test anxiety is common among students and has adverse effects on their exam performance. This study firstly focused on finding the prevalence of test anxiety. The second aim was to identify the predictors of test anxiety and its related variables among students who are going to take the university entrance exam.Method: Totally 436 students (girls=220, boys=216) who were randomly rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 27 publications
6
20
0
7
Order By: Relevance
“…The findings of this study demonstrated that more than half of the medical students had problematic test anxiety (52.30%). This prevalence is consistent with the reported magnitude of test anxiety from Saudi Arabia (53%) (27), the USA (55%) (28), and Turkey(48%) (29).…”
Section: Main Findingssupporting
confidence: 89%
“…The findings of this study demonstrated that more than half of the medical students had problematic test anxiety (52.30%). This prevalence is consistent with the reported magnitude of test anxiety from Saudi Arabia (53%) (27), the USA (55%) (28), and Turkey(48%) (29).…”
Section: Main Findingssupporting
confidence: 89%
“…This prevalence is consistent with the reported magnitude of test anxiety from Saudi Arabia (53%) (27), the USA (55%) (28), and Turkey(48%) (29).…”
Section: Main Findingssupporting
confidence: 89%
“…It was seen that when the topic of the university entrance exam came up, the participants frequently express their feelings of fear, discomfort, anxiety, despair, alarm and panic, all of which are emotional dimensions of anxiety (Türe et al, 2006;Kavakcı et al, 2014). As a matter of fact, the presence of an exam itself is a source of anxiety (Şad & Şahiner, 2016).…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%